2011
DOI: 10.1007/s00210-011-0660-8
|View full text |Cite
|
Sign up to set email alerts
|

MPP+-induced toxicity in the presence of dopamine is mediated by COX-2 through oxidative stress

Abstract: Accumulating evidence suggests that endogenous dopamine may act as a neurotoxin and thereby participate in the pathophysiology of Parkinson’s disease (PD). Cyclooxygenase-2 (COX-2) has been implicated in the pathogenesis of PD due to its ability to generate reactive oxygen species (ROS). Inhibition of COX-2 leads to neuroprotection by preventing the formation of dopamine-quinone. In this study, we examined whether dopamine mediates 1-methyl-4-phenylpyridinium (MPP+)-induced toxicity in primary ventral mesencep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…ROS play an important role in NLRP3 inflammasome activation (Tschopp and Schroder, ; Bauernfeind et al, ). Because COX‐2 is able to generate ROS (Fraser, ; Hsieh et al, ), we investigated whether COX‐2 regulates ROS production in response to LPS and ATP stimulation. We found that LPS‐induced ROS production was not affected by the COX‐2 inhibitor (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS play an important role in NLRP3 inflammasome activation (Tschopp and Schroder, ; Bauernfeind et al, ). Because COX‐2 is able to generate ROS (Fraser, ; Hsieh et al, ), we investigated whether COX‐2 regulates ROS production in response to LPS and ATP stimulation. We found that LPS‐induced ROS production was not affected by the COX‐2 inhibitor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ROS not only plays an important role in the priming step of NLRP3 inflammasome, but also regulates the activation step of the NLRP3 inflammasome (Tschopp and Schroder, ). The induction of COX‐2 expression leads to PGE 2 production and is usually accompanied by an increase in ROS levels (Fraser, ; Hsieh et al, ). Conversely, the inhibition of COX‐2 decreases ROS generation in human promonocytic cells infected by C. pneumonia (Mouithys‐Mickalad et al, ) and in myeloid‐derived suppressor cells and macrophages from tumor‐bearing mice (Veltman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mesencephalic dissociated neurons were prepared from the ventral mesencephalon of E14 rat (Sprague–Dawley) foetus as previously (Hsieh et al, 2011). Experimental protocols were in accordance with Home Office and institutional guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The apoptosis assay was performed as described before (Hsieh et al, 2011). Apoptosis was detected by Hoechst 33258 staining (Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
“…More specific blockade of inflammation has been achieved successfully with inhibitors of COX-2 (Sanchez-Pernaute et al, 2004), which has been shown to be increased in PD SN (Teismann et al, 2003). COX-2 can induce DA oxidation and NFκB-induced inflammatory responses in microglia (Schwieler et al, 2006; Hsieh et al, 2011); additionally it induces prostaglandin production that triggers the peripheral immune system (Font-Nieves et al, 2012). …”
Section: Immunomodulation As a Therapy For Pdmentioning
confidence: 99%